Selective and sensitive Escherichia coli detection based on a T4 bacteriophage‐immobilized multimode microfiber. Issue 9 (10th May 2018) - Li, Yanpeng; Ma, Hui; Gan, Lin; Gong, Andong; Zhang, Haibin; Liu, Deming; Sun, Qizhen
Abstract : Escherichia coli bacteria have been found to be responsible for various health outbreaks caused by contaminated food and water. Accurate and rapid test of E. coli is thus crucial for protecting the public health. A fast‐response, label‐free bacteriophage‐based detection of E. coli using multimode microfiber probe is proposed and demonstrated in this article. Due to the abrupt taper and subwavelength diameter, different modes are excited and guided in the microfiber as evanescent field that can interact with surrounding E. coli directly. The change of E. coli concentration and corresponding binding of E. coli bacteria on microfiber surface will lead to the shift of optical spectrum, which can be exploited for the application of biosensing. The proposed method is capable of reliable detection of E. coli concentration as low as 10 3 cfu/mL within the range of 10 3 to 10 7  cfu/mL. Owing to the advantages of high sensitivity and fast response, the microfiber probe has great potential application in the fields of environment monitoring and food safety. Abstract : Pathogenic Escherichia coli is a considerable threat to public health owing that the consumption of food or water contaminated by E. coli has great damage to human body. In this work, a high sensitive and fast‐response E. coli sensor based on bacteriophage immobilized multimode microfiber is proposed. The proposed technologies has great potential application in the fields of environment monitoring and food safety.